Aplikasi Prediksi Permintaan Produk Dengan Metode Simulasi Monte Carlo Berbasis Web - Achmad Shofiyuddin Al Farisi; Abdul karim; Sapto Hadi Riono (CV. Akira Java Bulu, 2024)
Green Belt is a company that is growing rapidly in the village of lembung pemekasan. The products available are various, such as Mangrove Coffee, Mangrove Tea, Bidara Tea, Mangrove Honey, and Wedang Jahe Merah. Uncertain sales figures for each product ordered, sometimes make it difficult for CV Sabuk Hijau owners to analyze existing sales data and manage products to be produced. cases of sales that go up or down significantly within a certain period resulting in a shortage or excess stock of raw materials for the products being sold, problems like this often occur due to the absence of tools, whether in the form of hardware or software that can help to increase the availability of products and raw materials in the market. next period. using the Monte Carlo simulation method with a case study in CV. Green Belt As a calculation tool for predicting product sales which is still done manually, with this web-based application built, it is expected to be an effective and accurate product demand data analysis tool, and provide a more optimal decision in this study using sales history data. 2021. After 12 trials of random number values, it will be known the main product with the most demand for the next period according to the simulated past data.